Systematic Literature Review: An Analysis of The Use of Cobit 5 for The Maturity Level of E-Government in Indonesia - Wiyarna, I Nyoman Adi; Yopan, Muhamad (Green Publisher Indonesia, 2025)
This study examines the use of COBIT 5 in evaluating the maturity of e-Government initiatives in Indonesia through a Systematic Literature Review (SLR). A total of 20 relevant Scopus-indexed journal articles published between 2014 and 2023 were selected using purposive sampling techniques. The study aims to identify which COBIT 5 domains are most frequently applied, the measurement approaches used, the types of government organizations involved, and how COBIT 5 contributes to improving digital governance. The findings reveal that the most utilized domains are EDM (Evaluate, Direct, and Monitor), APO (Align, Plan, and Organize), and MEA (Monitor, Evaluate, and Assess). Surveys and questionnaires are the predominant research methods, and most studies report maturity levels at stage 2 (Repeatable) or 3 (Defined). Several research gaps were identified, including the limited number of longitudinal studies, lack of standardized implementation across agencies, and minimal integration of COBIT 5 with other IT governance frameworks such as ITIL or ISO 27001. The study concludes that a more comprehensive, consistent, and integrated use of COBIT 5 can offer better insights into the digital maturity of public institutions. The findings contribute to the literature by outlining research trends, identifying limitations, and offering directions for future studies.